Orthopedic trauma or surgery does not effect on cognitive or behavioral capability of rats (Annals of Medical Research, 2021)
Aim: The aim of this study is to investigate the probable effects of orthopedic trauma/surgery on anxiety, memory and learning capability in rats. Material and Methods: Twenty-one Wistar albino rats grouped into three as control, sham operated, and tibia fracture. In control group, any surgery or fracture was done whereas in sham group the tibia of rats was fixed with intramedullar Kischner wire. In tibia fracture group, a closed fracture was occurred with Bonnarens and Einhorn's guillotine device then intramedullar Kischner wire sends to tibia. All rats were evaluated for memory, anxiety, and learning via behavioral tests respectively; water-maze test, elevated plus arm test and shuttle box test. Results: One month after the fractures were done and the bone healing was seen on X-ray at all rats. According to the behavioral tests results, there was not any statistically difference between groups in terms of anxiety, learning capability, locomotor activity and memory (p>0.05). Conclusion: Our results showed that, the orthopedic trauma or surgery itself does not affect the anxiety, learning capability, locomotor activity and memory in rats.